POLYMORPHISM of NUCLEOTIDE SEQUENCES of GENES THAT DETERMINE the VIRULENCE of ENTOMOPATHOGENIC FUNGUS Beauveria bassiana (Experimental biology, 2016)
It has been selected primers used for genotyping of three closely related Beauveria bassiana strains of different origin based on the analysis of nucleotide sequences of the inducible genes of the fungus that are involved in the pathogenesis of fungal infections of insects. Most of the sequences of genes of the three strains had homology at the level of 98-100 %, but the phase sequence of the gene encoding the excreted lipase (Slip), were significantly more polymorphic (homology 89-90 %). The use of this locus as a biogeographic molecular marker allowed to clearly differentiate strains of differing origin.
Keywords: Beauveria bassiana; genetic polymorphism; molecular marker; excreted lipase.